Development and validation of a stability indicating high performance liquid chromatography method for trimethobenzamide - Narayana Swamy; Venkata Krishna Reddy; Poonam Thorat; Pinaki Sengupta (Universidade de São Paulo, 2020)
A simple, accurate, precise and robust stability indicating RP-HPLC assay method has been developed for the estimation of trimethobenzamide in stress sample. An isocratic separation of trimethobenzamide was achieved on Kromasil 100 C-18 column (250 X 4.6mm, 5µ) with a flow rate of 1.0 ml/min and by using a photodiode array detector to detect the analyte at 213nm. The optimized mobile phase consisted of methanol: ammonium formate (44:56, v/v). The drug was subjected to different forced degradation conditions according to ICH guidelines including acid, base, neutral hydrolysis, oxidation, photolysis and thermal degradation. Degradation products were found only in basic and oxidative degradation conditions. All the degradation products got eluted in an overall analytical run time of 12min. The developed analytical method has been validated according to the ICH guidelines. Response of trimethobenzamide was linear over the concentration range of 0.5-50µg/mL (r2 = 0.999). Accuracy was found to be in between 94.03% to 100.39%. Degradation products resulting from the stress studies did not interfere with the detection of the analyte.